Photodegradation of polystyrene microplastics exposed to natural sunlight - Kilinc, Zeynep; Yesilay, Gamze; Cetin, Demet; Suludere, Zekiye; Rashdan, Suad; Hazeem, Layla; Bououdina, Mohamed; Kyzas, George Z. (ELSEVIER SCIENCE SA, 2025)
In the present study, we investigated the photodegradation of polystyrene microplastics (PS-MPs) exposed to natural sunlight over an extended period. Changes in particle size, surface charge, morphology, and chemical structure of PS-MPs were evaluated using Dynamic Light Scattering (DLS), Zeta potential measurements, Scanning Electron Microscopy (SEM), and Raman spectroscopy. Our findings revealed that exposure to natural sunlight significantly accelerates MP degradation process, resulting in pronounced fragmentation and chemical alterations compared to samples kept in dark conditions. While degradation occurs in the dark, light enhances the process. Therefore, researchers conducting studies on the toxicity of MP should include photodegradation parameter in the environmental impact assessment of MPs. Our findings highlight the importance of photo-degradation in understanding the environmental fate and impact of PS-MPs. Further research can focus on the ecological implications of these chemical changes and the interactions of degraded particles with marine biota.
Keywords: Phototransformation; Plastisphere; UV exposure; Seawater; ORGANIC-COMPOUNDS; PLASTIC DEBRIS; DEGRADATION; MICRO; NANOPLASTICS; AGGREGATION; KINETICS; SORPTION; HEALTH; Chemistry